Tailoring a chromogenic diketopyrrolopyrrole based probe for cyanide ion detection-applications in capsules and Arduino programming device - Kim, Hyunseo; Jayasudha, Palanisamy; Manivannan, Ramalingam; Son, Young-A (Journal of photochemistry and photobiology. A, Chemistry., 2025)
[Display omitted] •A new chromogenic probe DPP was designed and synthesized for cyanide sensing.•The low detection limit of 1.03 μM (UV–vis) and 5.84 nM (fluorescence) was found.•The electronic Arduino device was employed to detect cyanide ion.•Developed a test strip and polysulfone capsules with the probe for cyanide sensing. Though some anions are essential to our body’s metabolic processes, even in very little amounts, the cyanide ion is exceedingly toxic and harmful to people, animals, and the environment. A diketopyrrolopyrrole and benzaldehyde based moieties as binding sites has been developed and characterized by DFT and various spectral methods to detect cyanide ions. This probe DPP (4′-(2,5-diethyl-3,6-dioxo-2,3,5,6-tetrahydropyrrolo[3,4-c]pyrrole-1,4-diyl) dibenzaldehyde) shows impressive detection signals together with an easysynthesis procedure, quick reaction time, extraordinary selectivity, and good sensitivity. The orange color of the probe solution turns colorless when cyanide ion solution is added, making cyanide ion recognition visible to the naked eye. Crucially, the probe did not exhibit any signs of interference from possibly competitive ions, indicating its biological compatibility, with a detection limit of 1.03 μM (UV–vis) and 5.84 nM (fluorescence) for the cyanide ion recognition. The HRMS data demonstrate that the probe works with an addition reaction mechanism to bind with cyanide ion. The range of applications for cyanide probes is greatly increased as a result of its ability to sense cyanide ions effectively in variable matrices, including test strips, water, polysulfone capsules, and electronic Arduino devices.